1993
DOI: 10.1111/j.1365-2672.1993.tb01588.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of applying lactic acid bacteria at ensiling on the aerobic stability of silages

Abstract: T h e effect of applying commercial lactic acid bacteria inoculants at ensiling on the aerobic stability of silages was studied under laboratory conditions. T h e silages used were wheat, hedysarum, corn and various sorghum cultivars at various stages of maturity. T h r e e inoculants were used, two containing Lactobacillus plantarum, Enterococcus faecium and Pediococcus acidilactici (HIM F, Medipharm, USA and SiI-All, Alltech, U K ) and one containing Ent. faecium (Lacticil, M74, Medipharm, Sweden). T h e ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
147
2
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 11 publications
14
147
2
4
Order By: Relevance
“…<0.20 (Lima et al, 2011). Therefore, it may be speculated that the aerobic stability (Weinberg et al, 1993;Kung and Ranjit, 2001;Danner et al, 2003) of all silages can be disputed. The relative high proportions of acetic acid are difficult to explain but they may be related to a relative lack of rapid fermentable carbohydrates in OPF.…”
Section: Fermentation Qualitymentioning
confidence: 99%
“…<0.20 (Lima et al, 2011). Therefore, it may be speculated that the aerobic stability (Weinberg et al, 1993;Kung and Ranjit, 2001;Danner et al, 2003) of all silages can be disputed. The relative high proportions of acetic acid are difficult to explain but they may be related to a relative lack of rapid fermentable carbohydrates in OPF.…”
Section: Fermentation Qualitymentioning
confidence: 99%
“…4) Silage of high fermentation quality often permits the growth of spoilage yeasts due to lack of large amounts of VFAs. 5) Thus, it is difficult to prevent aerobic spoilage of silage of high fermentation quality.…”
mentioning
confidence: 99%
“…Higher CO 2 production in silage indicates the activity of yeasts and moulds, which cause a rise in temperature and reduce the quality of silage (Woolford, 1990;Ashbell et al, 1991). Weinberg et al (1993) concluded that residual WSC and LA were both substrates for yeast and mould growth, and that AA inhibited the growth of these organisms. The aerobic stability of the control soybean silage was poor, based on the intensive CO 2 production, increases in pH, and a rise in temperature and yeast and mould populations, compared with the treated silages (Table 3).…”
Section: Days Of Ensiling Phmentioning
confidence: 99%
“…Higher residual WSC in silage may be beneficial to ruminants, since it supplies energy to animals. However, residual WSC in silage may serve as substrate for aerobic microbes during the feeding-out phase (Weinberg et al, 1993).…”
Section: Days Of Ensiling Phmentioning
confidence: 99%